Penguatan Karakter Murid melalui Penerapan Kurikulum Mandiri di Sekolah Guna Mencegah Demoralisasi Murid - Abdul Holik Maulana; Juntika Nurihsan; Dede Margo Irianto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Character education in schools plays a strategic role in forming strong personalities in students to prevent demoralization. This article aims to examine the importance of character education in developing a tough and ethical personality, as well as exploring how the integration of moral values ​​can protect students from the effects of demoralization. The independent curriculum provides flexibility for schools to develop learning models that support character strengthening. This research uses a qualitative literature study method by collecting data obtained from books, journals and credible references according to the topic raised to strengthen the information studied. Based on literature analysis, it was found that the implementation of effective character education in the independent curriculum was able to minimize the impact of student demoralization. The research results show that effective character education not only builds strong personalities, but helps students develop positive attitudes. Character education is a solution in preventing moral crises through independent curriculum-based learning. Through the integration of character values ​​in learning, self-development, extracurricular activities, and habituation, students are able to demonstrate more moral behavior. In addition, collaboration between schools and parents on character education can prevent demoralizing behavior.